Effects of Psychoactive Plants on Male Sexual Function - Olorunfemi Oyewole Babalola; Olamide Wilson Fasakin (Journal of Psychosexual Health)
Sexual function/dysfunction are crucial factors that determine the quality of life of an individual. In order to avoid hypoactive sexual desire and lack of sexual satisfaction, many people consume aphrodisiac agents which enhance libido and sexual desires. Psychoactive plants are claimed to have aphrodisiac properties. In folklore, a number of natural products derived from these plants, including crude extracts and aphrodisiac concoctions, are consumed to mediate sexual motivation, increased desire, prolonged duration, and alertness. Psychoactive plants possess chemical compounds that most likely evolved as allelochemicals but, when taken by humans, target specific neural receptors, affecting emotion, perception, and cognition. Due to the diverse psychotropic effects of these plants, they have been utilized as medicines and in religious rites from ancient times. The historic use, toxicological profile, and effects of psychoactive plants on sexual function were briefly examined in this article.